Fifth annual report - Mew, E. B. ; Miller, Mary F. ; Norman, E. M. ; Roberts, D. ; Galbraith, H. ; Worden, M. ; Daukes, A. ; Waterworth, E. M. ; Mottram, D. B.; Capener, Norman (1932)
1932 1932 1930s 86 pages : illustrations Devonian Association for Cripples' Aid. EXTRACT FROM CONSTITUTION, RULES AND REGULATIONS. AIMS AND OBJECTS 1. To establish within its area an Orthopaedic Hospital School and Orthopaedic Clinics in connection with it. 2. To take such further action as experience may suggest and circumstances permit, for the welfare of cripples of all ages and both sexes within the area served by the Association. (Ref. Part 1, section 2, paras 1 and 2) A General Meeting shall be held annually, and the following persons shall be entitled to receive an invitation and to vote :— (a) Members of the General Purposes and Hospital Management Committees. (b) Hon. Clinic Secretaries and two Delegates from each District Committee. (c) All Annual Subscribers of not less than one guinea to the Association's Fund whose Subscription for the current year has been paid. (d) All donors of an amount of £5 and upwards during the preceding year. (The donor of £50 shall be entitled for life to attend the General Meetings. The Annual General Meeting shall be summoned by the General Purposes Committee and shall be held, if possible, within three months after the end of the financial year, and at least one calendar month's notice shall be given of the date. The Audited accounts shall be available for inspection in the Secretary's Office at the Hospital seven days before the Annual General Meeting. The financial year shall run from January 1st to December 31st. A General Meeting to consider any special business may be summoned at fourteen days' notice — (a) By the General Purposes Committee or (b) On a written application requiring the Chairman to issue the necessary notices, signed by not less than fifteen of those persons eligible to attend and to vote at an Annual General Meeting. (Ref. Part 1. section 5). 292/841.51/2/2